Paradoxical Sleep Deprivation Modulates Tyrosine Hydroxylase Expression in the Nigrostriatal Pathway and Attenuates Motor Deficits Induced by Dopaminergic Depletion - M.S. Lima, Marcelo; L. Andersen, Monica; B. Reksidler, Angela; C. Ferraz, Anete; A.B.F. Vital, Maria; Tufik, Sergio (CNS & Neurological Disorders - Drug Targets, 2012)
The nigrostriatal pathway is very likely involved in sleep regulation, considering the occurrence and high prevalence of sleep-related disorders in patients with Parkinson's disease. Indeed, dopaminergic neurons in the ventral tegmental area were recently shown to fire in bursts during paradoxical sleep (PS), but little is known about the activity of the nigrostriatal dopamine (DA) cells in relation to PS. In view of that we hypothesized that paradoxical sleep deprivation (PSD) may play a relevant role in nigrostriatal tyrosine hydroxylase (TH) expression and, subsequently, in sleep rebound. The present study was designed to determine the effects of PSD in the nigrostriatal pathway in mice by means of neurochemical and behavioral approaches. Intraperitoneal reserpine (1 mg/kg) associated to α-methyl-p-tyrosine (αMT) (250 mg/kg) to produce catecholamine depletion, or rotenone (10 mg/kg) to increase striatal DA turnover were injected 30 min before the 24 h of PSD. Catalepsy and open-field tests indicated that motor deficits induced by reserpine-αMT were counteracted by PSD, which, in contrast, potentiated the motor impairment induced by rotenone. Besides, PSD produced down-regulation on TH expression within the substantia nigra pars compacta and striatum, without affecting the number or the optical density of dopaminergic neurons present in the respective areas. Interestingly, PSD potentiated the downregulation of TH expression in the substantia nigra pars compacta and striatum induced by the co-administration of reserpine-αMT. These results reinforce the notion of a strong participation of DA in PS, as a consequence of the modulation of TH protein expression in the nigrostriatal pathway.
Keywords: reserpine